Analysis Of The Indonesian Foreign Trade Policy With Argentina In Period 2008-2013 - Zuhri, Saefudin; Asyidiqi, Habi (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This research aims to understand the reasons behind Indonesia trade with Argentina in the period 2008-2013. The formulation of the problem in this research is the “Why Indonesia keep doing trade with Argentina in the years 2008 to 2013 but the balance of trade deficit?”. Through the frame of economic nationalism, the research found that in line with the value of a strong political history between the two, Indonesia had the interests of market access (trade policy) and strengthening of the domestic industry (industrial policy). Market access in this case related interests of Indonesia who made Argentina as a hub in the region of South America. But in terms of strengthening the domestic industry, not apart from the strengthening of the ranching industry needs through imports of animal feed from Argentina.